Genetic structure and historical diversification of catfish Brachyplatystoma platynemum (Siluriformes: Pimelodidae) in the Amazon basin with implications for its conservation - Ochoa, Luz Eneida [UNESP]; Pereira, Luiz Henrique G.; Costa-Silva, Guilherme Jose [UNESP]; Roxo, Fabio F. [UNESP]; Batista, Jacqueline S.; Formiga, Kyara; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP] (Wiley-Blackwell, 2015)
Brachyplatystoma platynemum is a catfish species widely distributed in the Amazon basin. Despite being considered of little commercial interest, the decline in other fish populations has contributed to the increase in the catches of this species. The structure, population genetic variability, and evolutionary process that have driven the diversification of this species are presently unknown. Considering that, in order to better understand the genetic structure of this species, we analyzed individuals from seven locations of the Amazon basin using eight molecular markers: control region and cytochrome b mtDNA sequences, and a set of six nuclear microsatellite loci. The results show high levels of haplotype diversity and point to the occurrence of two structured populations (Amazon River and the Madeira River) with high values for F-ST. Divergence time estimates based on mtDNA indicated that these populations diverged about 1.0Mya (0.2-2.5Mya 95% HPD) using cytochrome b and 1.4Mya (0.2-2.7Mya 95% HPD) using control region. During that time, the influence of climate changes and hydrological events such as sea level oscillations and drainage isolation as a result of geological processes in the Pleistocene may have contributed to the current structure of B.platynemum populations, as well as of differences in water chemistry in Madeira River. The strong genetic structure and the time of genetic divergence estimated for the groups may indicate the existence of strong structure populations of B.platynemum in the Amazon basin.
Keywords: Biodiversity; climate oscillation; Madeira River; marine transgression; Neotropical fishes; phylogeography